Improving IPS (Social Science) Understanding In The Physical Condition of The Indonesian Region through Cooperative Learning with Learning Together Models - Rofi'ah, Siti Zahrotur (Metafora: Education, Social Sciences and Humanities Journal, 2020)
Many students underestimate Social Sciences, because they consider Social studies are easy lessons. According to research conducted in class VIII A, classroom teachers often use the lecture method, group assignments and never use innovative learning methods, so students are not actively involved in learning. Students never answer questions from the teacher because they feel fear and shame. Students also never express their opinions when asked by the teacher. It is known from the evaluation of learning outcomes that only 3 (12%) students from 25 students have a good level of understanding of the subject matter. This shows the learning outcomes are still low and still need to be sought for the selection of learning methods that are more appropriately adapted to the material to be delivered by the teacher. The location of the repairs was carried out at YPI Darussalam 1 Cerme Gresik Middle School For Students VIII / A Semester I Academic Year 2018/2019 which amounted to 25 students involving 1 colleague to help conduct monitoring and observation during the learning process, Observers' results can be explained that by applying cooperative learning the learning together model obtained the average value of the first cycle of student learning achievement was 52.4 and learning completeness reached 12% or there were 5 students from 25 students have finished studying. These results indicate that in the first cycle classically students have not yet finished learning, because students who obtain a value of â‰¥ 69 are only 12% smaller than the desired percentage of completeness which is equal to 70%. This is because students are new and unfamiliar with the new methods applied in the teaching and learning process. Â Whereas in the second cycle the average student achievement score is 84 and learning completeness reaches 100% or there are 25 students from 25 students who have finished learning. These results indicate that in the second cycle learning completeness has been fulfilled. This means that cooperative learning learning together model can improve social studies comprehension in the material physical condition of Indonesia in class VIII A YPI Darussalam 1 Cerme Middle School Greseik Academic Year 2018/2019.